Evaluasi Kelayakan UMKM Tahu dan Tempe di Tambusai Utara - Kafrina, Kafrina; Novianisa, Ariela; Syafitri, Kiki; Syah, Rahmat; Putra Efendi, M. Reynaldi (Jurnal Rumpun Ilmu Ekonomi, 2023)
To assess the feasibility of a business venture, both financial and non-financial factors are considered. The evaluation of feasibility involves analyzing non-financial elements, with a particular focus on production and marketing aspects. The financial aspects of Tofu and Tempeh Sukses Jaya's commercial production were analyzed using objective metrics such as payback period (PP), net present value (NPV), internal rate of return (IRR), and profitability index (PI) to determine its overall feasibility. Based on the analysis, it was concluded that the business is feasible due to its advantageous location and convenient accessibility. The Tofu and Tempeh Sukses Jaya business seems viable due to its strategic and easily accessible location, modern technology, and straightforward production process. Feasibility is ensured by high product quality, imported raw materials, competitive pricing, extensive distribution channels, and effective promotional efforts by the owner to ensure consumer awareness. The financial analysis indicates that the Tempeh Tofu business could be viable over a 10-year project duration with a 10 percent discount rate. The business has a 6-month payback period (PP), a net present value (NPV) of Rp 161,565,200, a profitability index (PI) of 1.6%, and an internal rate of return (IRR) of 30%, all of which suggest the business's financial feasibility.